2012
DOI: 10.1007/s10212-012-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Making the difference with active parenting; forming educational partnerships between parents and schools

Abstract: Although parental involvement is often a priority on the quality agenda of schools for primary and secondary education, it is still not usual to involve parents as an educational partner in the actual learning process of their child. Rather than adopting an open approach, teachers tend to tell parents what they should do or keep them at a safe distance. At the same time, parents are increasingly becoming better informed, more critical and thus are more strongly positioned towards school. They address teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
2
20
0
4
Order By: Relevance
“…Our survey results revealed that more of the parents chose to be involved in their child's education at home than chose not to, that most of the parents were rarely involved in their child's education at school, and that the teachers were more likely to exclude than they were to include parents in the child's education at school. Our results confirm the view expressed by Oostdam and Hooge (2013) that, sometimes, instead of creating a dialogue with parents, teachers tend to tell parents what they should do or to keep them at a distance.…”
Section: Discussionsupporting
confidence: 94%
“…Our survey results revealed that more of the parents chose to be involved in their child's education at home than chose not to, that most of the parents were rarely involved in their child's education at school, and that the teachers were more likely to exclude than they were to include parents in the child's education at school. Our results confirm the view expressed by Oostdam and Hooge (2013) that, sometimes, instead of creating a dialogue with parents, teachers tend to tell parents what they should do or to keep them at a distance.…”
Section: Discussionsupporting
confidence: 94%
“…Naar welke vormen van ouderbetrokkenheid van belang zijn voor het prestaties van leerlingen, wordt nog volop onderzoek gedaan (e.g. Oostdam & Hooge, 2012;Sheldon, Epstein & Galindo, 2010). In de PIRLS-en TIMSS-schoolvragenlijst zijn er drie vormen van ouderbetrokkenheid aan de schoolleider voorgelegd: contact met ouders over individuele leerlingen, deelname van ouders aan schoolactiviteiten en activiteiten gericht op het voorlichten en informeren van ouders.…”
Section: Ouderbetrokkenheidunclassified
“…Ross (1994) shows that teachers with a higher perceived efficiency level exhibit enhanced student mastery of cognitive and affective goals. The wide-spread research and government programs on how to enhance family-school partnerships are entirely based on this positive link between parental and school motivation (Garcia 2004;Flynn 2011;Sanders 1996;Hoover-Dempsey et al 2002;Oostdam and Hooge 2013 among many others). To capture this positive link formally, we postulate:…”
Section: If Both the Schools And The Child's Parent L Choose A Positimentioning
confidence: 99%